Unveiling patenting strategies of therapeutics and vaccines: evergreening in the context of COVID-19 pandemic - Bacigalupo, María Lorena; Pignataro, María Florencia; Scopel, Carolinne Thays; Kondratyuk, Sergiy; Mellouk, Othoman; Chaves, Gabriela Costa (Frontiers in Medicine, 2023)
In the pharmaceutical sector, evergreening is considered a range of practices applied to extend monopoly protection on existing products. Filing several patent applications related to the same active pharmaceutical ingredient (API) is one of the most common manifestations of evergreening. During the COVID-19 pandemic, several health technologies were developed. This study aimed to analyze the extension of evergreening for selected health technologies for SARS-CoV-2 through patent filing strategies. Starting with the selection of three antivirals, one biological and two vaccines, a patent landscape was built based on public and private databases. Regarding these selected technologies, we analyzed some of the evergreening strategies used by different applicants, academic institutions or pharmaceutical companies and found a total of 29 applications (10 after the pandemic) for antivirals, 3 applications for a biological drug (1 after the pandemic), and 41 applications for vaccines (23 after the pandemic). Despite differences among the technologies, a common aspect found in all analyzed cases is the intense patent filing after the pandemic, aligned to the fact that those technologies were moving through the R&D process up to regulatory approval. The evergreening approach pursued has already been found in other diseases, with the risk of monopoly extension and also bringing legal uncertainty due to the lack of transparency of newer patent applications covering specific medical indications. Therefore, efforts to address evergreening should be pursued by countries, including the adoption of a public health approach to the patent examination of those technologies to prevent the granting of undeserved patents.